Talent selection criteria for olympic distance triathlon - Bottoni, A.; Gianfelici, A.; Tamburri, R.; Faina , M. (Journal of Human Sport & Exercise, 2011)
Talent Selection allows to optimize the resources available for sporting talent in order to design the best strategy to achieve top level sporting results. Because of the unknown aspects of the performance model in Olympic triathlon the TS variables and their relationship with a future performance are far-off from being identified in order to make a talent prospective study possible. Currently most triathlon federations evaluate only the juvenile performance expressed in time trials test on swimming and running. The aim of the present study was to find the most appropriate variables for the Talent Selection in Olympic Triathlon, verifying those widely used by means of a retrospective research about particular juvenile features recognized in top world triathlon athletes. The variables are considered as input variables of a Talent selection model based on Fuzzy Logic that overcome the limits of traditional models based on cut-off selection. The present findings indicate that the exclusive evaluation of juvenile running and swimming performance in order to select triathlon talent is not appropriate. Diagnosis criteria should include several other variables that should also take into account mental ability, speed of abilities development, utilization of endogenous and exogenous resources, load and stress tolerance as several leading countries have done recently.